Potentials for Efficiency Increase in Modern Freight Forwarding - Krajewska, Marta Anna. (Gabler Verlag : Imprint: Gabler Verlag, 2008)
The freight forwarding market has become extremely demanding for the professional carriers in a road transport. Apart from decreasing prices and increasing competition, freight forwarders have to cope with the fact that demands fluctuate on a short-term basis and that fast adjustments to the constantly changing customer’s needs are essential. From this perspective, searching for unexploited possibilities to optimize performance has proved to be an effective means to realize cost-saving targets and can make the difference between ‘to be or not to be’ for many freight forwarders. On the basis of an analysis conducted in a freight forwarding company, Marta Anna Krajewska identifies two levels of improving logistics performance. First, she demonstrates that on the local level the automated operational transportation planning increases the planning quality and influences mid- and long-term planning issues. Secondly, the results show that on the global level the proposed horizontal collaboration.